Situation Analysis of Full Time Physicians Plan Using SWOT Model in Iran - Hossein Dargahi; Rostam Zalvand (Tehran University of Medical Sciences, 2019)
Background: Physicianschr('39') full time attendance is related to increment of many hospitals performance. Regarding the present challenges, this study aimed to analyze this plan using SWOT technique and present TOWS model in Tehran University of Medical Sciences (TUMS).   Materials and Methods: This study was a descriptive-analytical and cross-sectional one conducted during 2016-2017. Based on Cochran formula, 234 full time attending physicians randomly selected using simple randomization method. The research tool was a researcher made SWOT questionnaire which confirmed its content validity and reliability. Collected data was analyzed by SPSS software using SWOT technique and suggested TOWS strategic model.   Results: The most valuable weaknesses of mentioned plan were inappropriate coordination of physicians; lack of compensatory system, and the most important strengths were employment of young physicians and better education for medical students. The most important opportunities and threads of mentioned plan were establishment of competitive work between public and private hospitals and burnout and dispensing of experienced physicians moving to private sector, respectively.   Conclusion: Based on study findings, TOWS model strategies can be suggested for improvement of the plan.